2013
DOI: 10.1038/ejcn.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

Increased sedentary behaviour is associated with unhealthy dietary patterns in European adolescents participating in the HELENA study

Abstract: Adolescents' DPs are related with the time spent in several sedentary behaviours. Such findings may help to generate interventions focusing on decreasing unhealthy dietary habits and specific sedentary behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 37 publications
5
24
1
1
Order By: Relevance
“…Santaliestra-Pasias et al [9] reported an association [29] observed that TV viewing was associated with energy-dense snack consumption. In both studies, 'healthier' dietary patterns were consistently associated with less time spent in front of a screen and more 'unhealthy' dietary patterns were associated with more time spent in front of a screen [30,31]. An often observed sedentary behaviour in preschool children is quiet play.…”
Section: Discussionmentioning
confidence: 90%
“…Santaliestra-Pasias et al [9] reported an association [29] observed that TV viewing was associated with energy-dense snack consumption. In both studies, 'healthier' dietary patterns were consistently associated with less time spent in front of a screen and more 'unhealthy' dietary patterns were associated with more time spent in front of a screen [30,31]. An often observed sedentary behaviour in preschool children is quiet play.…”
Section: Discussionmentioning
confidence: 90%
“…The findings suggest that high screen time in early adolescence may be an important indicator of later overweight among normal-weight children, making normal-weight children with high screen times a particularly relevant group for targeted preventive measures. It seems likely that high screen time in early adolescence may be a risk factor in terms of subsequent unhealthy habits and weight gain, as screen time tends to track through adolescence ( 13 ) and is often associated with unhealthy dietary patterns ( 39 ) . In our sample, high screen time was associated with a high intake of the snacking eating pattern at baseline ( P <0·05, data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Western regions (3,4) and from Arab countries (5,6) indicated that adolescents and young people have poor dietary habits, such as the tendency to skip breakfast and having a low intake of fruit, vegetables, milk and fish, and a high intake of sugar-sweetened beverages, fast foods and sweets, and they also skipped breakfast. Furthermore, inactivity and sedentary habits have been highly prevalent among adolescents and young subjects (5).…”
Section: Introductionmentioning
confidence: 98%